TUHAN, NABI, DAN NEGARA IDEAL "Telaah Atas Pemikiran Al-Farabi" - Gasim Yamani (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2021)
This article aims to explore the realms of al-Farabi's philosophical thought, by focusing on four problems: Is God unnecessary in the process of creating nature to know, think and even make nature the object of his thought? 2). How to interpret the influence of Imagination that underlies al-Farabi's theory of prophethood? 3). How is al-Farabi's view of the human soul? and 4). What is the ideal state form for al-Farabi? To answer this problem, the method used is library research research, with a philosophical approach. The research results obtained: First, God does not depend on nature as the object of his thought in the process of natural creation. Second, the Prophet, through his strong imaginative abilities, was not only able to deal directly with Mustafad's intellect, but was also able to translate the revelations that were sent down and transferred to us. Third, the soul has two powers, a theoretical power, namely the human thinking power that can distinguish and judge and is able to express different competences, and the practical power is the power that determines what human actions must be done. Fourth, the ideal country is a country whose leader is not only political, but also includes ethical issues.